2016
DOI: 10.17750/kmj2016-336
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of shear wave elastography and elastometry results in the endometrial pathology diagnosis in patients with secondary infertility

Abstract: Aim. To analyze the results of the application and to study the effectiveness of ultrasound shear wave elastography and elastometry in the endometrial pathology diagnosis in secondary infertility.Methods. Multiparameter ultrasound with shear wave elastography and elastometry modes (Shear Wave Elastography) was performed in 146 women of reproductive age (Aixplorer scanner, Supersonic Imagine, France). The main group (N1) included 101 women with secondary infertility: 43 patients with tuberculous lesions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The mean elasticity value for endometrium was 25.54 AE 8.56 kPa. There was only 1 study, by Diomidova et al, 14 that reported the elasticity characteristics of the normal endometrium, in which 46 healthy women were assessed by SWE, and a mean elasticity of 16.5 AE 1.0 kPa for the endometrium was found. The same equipment was used in their study, with a similar scale and Q-box size for measuring the elasticity values as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The mean elasticity value for endometrium was 25.54 AE 8.56 kPa. There was only 1 study, by Diomidova et al, 14 that reported the elasticity characteristics of the normal endometrium, in which 46 healthy women were assessed by SWE, and a mean elasticity of 16.5 AE 1.0 kPa for the endometrium was found. The same equipment was used in their study, with a similar scale and Q-box size for measuring the elasticity values as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HE, estrogen dependence of endometrial polyposis is also questionable, and the inflammatory theory comes to the fore, which has put forward a scientific position on the existence of two different pathogenetic types of endometrial polyposis – hormone-dependent and inflammatory ones [ 12 , 13 , 17 – 19 ], in which both bring changes in the immune system, inflammatory factors and hormonal disorders [ 3 , 10 , 14 16 ]. In the literature, the influence of persistent chronic inflammatory process of both bacterial and viral etiology on the development of female proliferative diseases is discussed, which activates angiogenesis, alteration of tissue by mast cells, pathological proliferation, and initiates further progression of endometrial pathology [ 11 , 21 , 24 , 26 ]. The etiological theory of polyp formation is ambiguous; issues of their prevention remain controversial when, according to scientific studies, the growth of polyps may be caused by the ovarian pathology (polycystic ovary syndrome, chronic inflammatory process of the uterine appendages, stromal tekomatosis), which can stimulate and support proliferative processes in the endometrium [ 11 , 21 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the influence of persistent chronic inflammatory process of both bacterial and viral etiology on the development of female proliferative diseases is discussed, which activates angiogenesis, alteration of tissue by mast cells, pathological proliferation, and initiates further progression of endometrial pathology [ 11 , 21 , 24 , 26 ]. The etiological theory of polyp formation is ambiguous; issues of their prevention remain controversial when, according to scientific studies, the growth of polyps may be caused by the ovarian pathology (polycystic ovary syndrome, chronic inflammatory process of the uterine appendages, stromal tekomatosis), which can stimulate and support proliferative processes in the endometrium [ 11 , 21 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations